Customers Inside, Customers Outside: Designing and Succeeding With Enterprise Customer-Centricity Concepts, Practices, and Applications - Lowenstein, Michael W (Business Expert Press, 2014)
Ebook from IG Library ; Over the past several years, leading companies have entered a period of major marketing and operational adjustment and convergence, or intersection. It's a reaction to a critical fact of life: Customers--not organizations-- now control the decision-making dynamics and how organizations are perceived. We are witnessing significant multichannel media application (and resultant omnichannel access by consumers), along with more effective and pervasive customer data gathering, analysis, and modeling. If you're observing these major shifts in your own organization, you'll need this book. Inside, you'll learn how to build proactive customer communication, improve relationships, drive positive brand perception, optimize channel selection and message personalization, and enhance employee-related factors (hiring, training, reward, recognition), all leading to superior customer experience and a customercentric culture. In addition, the author has incorporated content on 'Big Data' generation and analytics, which you'll master while scoring a direct hit to the moving target--your continuously changing, and increasingly independent, customer base.